FUZZY INFERENCE SYTEM TSUKAMOTO UNTUK PENENTUAN PENERIMA JAMKESMAS DENGAN MICROSOFT VISUAL BASIC DAN MYSQL - M Ghofar Rahman (Universitas Islam Lamongan, 2017)
The problem that existed in the health service agency in this case is the health center, namely the determination of the recipient of public health insurance (Jamkesmas), although in practice the determination of recipients Jamkesmas already using the computer, but only limited to the support and there is no system that can be used to support the retrieval Decisions based on existing variables. The decision support system for determining the members of Jamkesmas recipients, where the system is used to help determine the recipients of Jamkesmas to be provided in accordance with their respective groups to accelerate the work of determining the provision of Jamkesmas. The system can assist the puskesmas in determining the members of Jamkesmas beneficiaries in accordance with the appropriate class to the community who want to become the members of Jamkesmas beneficiaries at the Puskesmas. This decision support system using the Fuzzy Tsukamoto Method, which will provide a decision solution to the puskesmas in determining the members of the public health insurance (Jamkesmas).